Interdisciplinary recommendations document to improve adherence in patients with chronic inflammatory diseases: Adhing recommendations - Fernando Bermejo San José; Mireia Barceló Barceló-Bru; Miquel Ribera-Pibernat; José Luís Poveda-Andrés; Luciano Sanromán-Álvarez (Farmacia Hospitalaria)
Objective: Patient compliance in chronic inflammatory diseases is essential to achieve treatment effectiveness. The study objective is to develop a recommendations document for healthcare professionals to encourage treatment compliance. Methods: A sequential methodology was followed: 1. Systematic review of EBM Reviews, Embase and MedLine without time restriction of interventions on compliance in chronic inflammatory diseases. Studies were selected according to previously defined criteria (confirmed diagnosis of chronic inflammatory disease of patients included, assessment of adherence interventions and experimental study design). 2. Three expert workshops (hospital pharmacy, nursing and medical specialties) to elaborate recommendations. 3. Expert online voting about the degree of agreement with recommendations. 4. Final face to face consensus workshop. Results: A total of 1 115 papers were identified, 84 were fully reviewed and 30 were selected according to criteria. A preli minary list of 8 recommendations based on evidence was developed and discussed in the expert workshops. As a result, a new version of 14 recommendations was created. Later, online voting showed a high degree of agreement among experts: 7 out of 14 recommendations obtained unanimous approval; in the other 7, 1 to 3 experts were partially in disagreement. Recommendations without unanimous agreement were further reviewed and modified in the face to face meeting and final recommendations were approved unanimously. Conclusions: This consensus statement gathers all relevant aspects to be interdisciplinary considered to detect, monitor and assess medication adherence, involving the patient in the process. Further studies are needed to assess the impact of interventions to improve compliance in patients with chronic inflammatory diseases both in terms of adherence and in health outcomes